"But You're Not at All like Bertha": Contemporary (Black) Trans* Studies and Richard Wright's "Man of All Work". (27th September 2021) - Foster, Guy Mark
Abstract: This essay mines the intersections among contemporary trans* studies, black feminism, and black studies to reexamine Richard Wright's short story, 'Man of All Work' (1961), depicting a black heterosexual man's efforts to save his home from foreclosure by dressing in his wife's clothes to find work. Rather than engage these critical traditions in rigid identitarian terms, this essay uses such scholarship to examine how the author's farcical attempts to dramatize the cultural feminization of black men yields complex theoretical insights as to the impact of anti-black racism on the lived experiences of black people. A key insight from black studies is the tendency of US white supremacy to collapse black gender difference into sameness, thereby excluding black men and women from sexual difference. Highlighting the fungibility of black gender, this essay works these scholarly intersections to examine how the self-conscious exploitation of anti-black assumptions about the body creates the potential for unlikely intraracial solidarities to emerge.